Environmental coastal research: a systematic review for Azores and Cabo Verde, two peripherical Macaronesian archipelagos - Larrea, Ander; Torres, Paulo; Seijo, Cristina; Ventura, Maria Anunciação; Costa, Ana Cristina; Parente, Manuela Isabel; Lopes, Evandro; Castaño, Danko; Botelho, Andrea Zita (Frontiers in Marine Science, 2023)
There is a strong link between humans and the coastal zone, as it provides important services and resources. This paper aims to determine the existing environmental coastal research status in the Azores and Cabo Verde since research is essential for any decision support system. Some tools are fundamental to ensure the viability of the marine environments, such as Integrated Coastal Zone Management (ICZM), Marine Protected Areas (MPAs), and Marine Spatial Planning (MSP), which rely on existing knowledge. Effective implementation of marine plans can increase by developing a multi-perspective knowledge approach. This paper presents a systematic review of the archipelagos of the Azores and Cabo Verde through a comparative meta-analysis of the literature based on the PRISMA report to better understand the focus and status of research related to coastal zones, within and outside MPAs, along with marine spatial planning and management in the two socio-economic contexts. This will help to identify common issues, trends over the years, successes, and challenges, highlighting the specific interests of each country, identifying the knowledge gaps, promoting mutual learning, and pointing out possible paths for future convergence toward sustainable use of the ecosystems and conservation goals. Differences were found between the research made in both archipelagos, lacking research on important disciplines (reproduction, behavior, population dynamics, climate change, etc.), in Cabo Verde, compared to the Azores. This study also reveals that some research fields still need to be pushed forward to have broader knowledge in both areas.